Implementasi Media Visual Gambar untuk Perkembangan Kognitif Anak Usia Dini di Tadikal Al Fikh Orchard Pendamar Indah 2 Selangor Malaysia - Raoza, Vina (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Learning media greatly influences children's cognitive development, namely so that children are able to train their memory and logical thinking. Children's thinking and learning abilities can be improved by putting them into action or providing appropriate stimulation so that children's cognitive development can develop well. This research aims to find out the results of the implementation of the use of visual image media in improving the cognitive development of early childhood at Tadika Al Fikh Orchard Pendamar Indah 2, Selangor, Malaysia. This research method uses a qualitative approach with descriptive research type. Data collection was carried out through observation, interviews and documentation. The data analysis technique uses Miles and Huberman interactive analysis, then data validity is tested using the triangulation method. The research results show the implementation of visual image media with an interactive learning approach and direct experience in developing cognitive skills, which includes 1) Planning, namely to prepare images that will be used by students according to the theme, 2) Implementation, to prepare image media, in the form of picture cards , posters, photos, according to the learning theme. 3) Assessment that shows the results of the child's cognitive development. In conclusion, the implementation of visual media at Tadika Al Fikh Orchard Pendamar Indah 2 shows effective learning planning and implementation, but faces obstacles such as media size, which can be overcome with teacher training.